The effect of the components of King's spiritual intelligence group training on stigma in patients with cancer - Masoud Kashani Lotfabadi; Bibi Maryam Hashemi; Saeed Sarabian; Azam Mohammadi; Azam Salarhaji (Tehran University of Medical Sciences, 2020)
Background & Aim: cancer stigma is one of the Psycho-social consequences of a cancer diagnosis. It seems that spiritual intelligence training can reduce cancer stigma by enhancing spiritual intelligence. Therefore, the purpose of the present research was to determine the effect of the components of King's spiritual intelligence group training on stigma in patients with cancer. Methods & Materials: This randomized controlled clinical trial was carried out in Omid Oncology Hospital of Mashhad, Iran in 2018-19. The statistical population of the study included 54 patients with cancer who were then randomly divided into an intervention group (23 individuals) and a control group (27 individuals). The patients in the intervention group received King's spiritual intelligence group training (2008) for ten (90-minute) sessions, while the patients in the control group received routine care. The data collection instrument was Cancer Stigma Scale (patient version). The data were analyzed by SPSS-22 software using independent t-test, Man Whitney, paired t-test, and Wilcoxon statistical test. Results: The findings showed that there is no statistically significant difference between the intervention and control groups in terms of stigma total mean score for the pre-intervention phase (p>0.05). However, in terms of stigma total mean score changes between the post and pre-intervention phases, there was a significant difference between the scores of the intervention and the control group (p<0.001). Conclusion: Spiritual intelligence training is effective in reducing stigma among patients with cancer.